Hepatic Damage Induced By Fructose And Aspartame In Carbonated Drinks: Morphological And Histological Analysis In Adult Male Albino Rats - Faiza Shafqat; Muhammad Suhail; Ayesha Ali; Hafsa Nazeer; Sadia Iqbal; Saqib Mansoor (Journal of Rawalpindi Medical College)
Objective: The study aims to analyze the changes produced by fructose and aspartame in regular and zero-calorie carbonated drinks respectively on the morphology and histology of the liver of adult male albino rats.